The inhibition effect of anti-GPIIIa49–66 antibody on megakaryocyte differentiation - Pan, Ruimin; Wang, Jianhui; Nardi, Michael A.; Li, Zongdong (Thrombosis and Haemostasis, 2011)
We previously reported that patients with early-onset HIV-1 ITP developed a unique anti-platelet integrin GPIIIa antibody against the GPIIIa49–66 epitope. Anti-GPIIIa49–66 antibody-induced platelet fragmentation requires sequential activation of the platelet 12-lipoxygenase (12-LO) and NADPH oxidase to release reactive oxygen species (ROS). 12-LO is upstream of the NADPH oxidase pathway and 12(S)- HETE, the product of 12-LO, induces the same oxidative platelet fragmentation as anti-GPIIIa49–66. Since the megakaryocyte (MK) is the progenitor cell for platelets, we have investigated the effect of anti- GPIIIa49–66 on MK differentiation and, in particular, the potential role of anti-GPIIIa49–66 induced ROS in this process. We first show that polyclonal anti-GPIIIa49–66 antibody isolated from HIV-1 ITP patients inhibits MK proliferation 2.5-fold in in vitro culture of human cord blood CD34+ cells driven by thrombopoietin (TPO). We also observe a three-fold decrease in the number of MK colony-forming units in the presence of a human monoclonal anti-GPIIIa49–66 antibody. However, we could not detect ROS release in DCFH-loaded mouse megakaryoblastic cells L8057 treated with anti-GPIIIa49–66 antibody. In addition, 12(S)-HETE does not inhibit the in vitro differentiation of L8057 cells induced by TPO. In fact, we found a dose dependent increase in the percentage of CD41 positive cells (from 17.1% to 48.7%) in in vitro culture of L8057 cells treated with various concentrations of H2O2 (from 5 to 20 μM). We therefore conclude that the anti-GPIIIa49–66 antibody inhibits MK differentiation through β3 integrin signalling independent of ROS release.
Keywords: Thrombocytopenia; HIV; autoantibody